The correlation of neutrophil-lymphocyte ratio and platelet–lymphocyte ratio with nephropathy in patients of type 2 diabetes mellitus-a hospital-based study from South India - Aishwarya Mathew; Veena Jasmine Pinto (Asian Journal of Medical Sciences, 2025)
Background: Diabetes is a group of metabolic diseases characterized by hyperglycemia due to defects in insulin secretion, action, or both. Diabetic nephropathy is among the serious complications of diabetes. Albuminuria is used as a biomarker for diabetic nephropathy. There is evidence of inflammation leading to the development and progression of diabetic nephropathy. White blood cell count, platelet counts have been used as markers of inflammation. Aims and Objectives: This study aims to determine a correlation between neutrophil-lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), and diabetic nephropathy. Materials and Methods: This cross-sectional analytical study was done among 99 individuals availing of the Medical College Hospital services for 18 months. They were classified into three groups of thirty-three participants each, based on the urine albumin–creatinine ratio. The three groups were the normoalbuminuria, microalbuminuria, and macroalbuminuria groups. The NLR and PLR was calculated and compared among the three groups. Results: The mean NLR in diabetic patients with macroalbuminuria (2.68) was significantly higher than patients with normoalbuminuria (1.46) and microalbuminuria (1.80) (P=0.001). The mean PLR was also higher in diabetic patients with macroalbuminuria (156.80) when compared to patients with normoalbuminuria (90.94) and microalbuminuria (119.03) (P=0.001). Conclusions: Increased NLR and PLR levels are associated with diabetic nephropathy. A higher NLR and PLR value can indicate the progression of diabetic nephropathy due to worsening estimated glomerular filtration rate. NLR and PLR can be used as a simple prognostic marker for Diabetic Nephropathy.